MicroRNA-19b-3p dysfunction of mesenchymal stem cell-derived exosomes from patients with abdominal aortic aneurysm impairs therapeutic efficacy - Yuxiao Zhang; Xiaoran Huang; Tucheng Sun; Linli Shi; Baojuan Liu; Yimei Hong; Qing-Ling Fu; Yuelin Zhang; Xin Li (Journal of Nanobiotechnology)
Abstract Senescence of vascular smooth muscle cells (VSMCs) contributes to the formation of abdominal aortic aneurysm (AAA). Although mesenchymal stem cell exosomes (MSC-EXO) have been confirmed to restrict the development of AAA, their biological activity depends largely on the physiological state of the MSCs. This study aimed to compare the effects of adipose-derived MSC-EXO from healthy donors (HMEXO) and AAA patients (AMEXO) on senescence of VSMCs in AAA and explore the underlying mechanisms. An ApoE-/- mouse model of AAA was used to investigate the therapeutic effects of HMEXO, AMEXO or miR-19b-3p-AMEXO on AAA development. This in vitro model of AAA was established by treating VSMCs with Ang II (Angiotensin II). The senescence of VSMCs was determined by senescence-associated β-galactosidase (SA-β-gal) staining. The morphology of mitochondria in VSMCs was examined by MitoTracker staining. HMEXO exhibited superior capacity compared with AMEXO to inhibit VSMC senescence and attenuate AAA formation in Ang II–treated ApoE-/- mice. In vitro, both AMEXO and HMEXO inhibited Ang II-induced VSMC senescence via downregulation of mitochondrial fission. Notably, compared with HMEXO, the ability of AMEXO to inhibit VSMC senescence was significantly decreased. miRNA sequencing and the expression of miR-19b-3p was significantly decreased in AMEXO compared with HMEXO. Luciferase assay suggested that MST4 (Mammalian sterile-20-like kinase 4) is a potential target of miR-19b-3p. Mechanistically, miR-19b-3p in HMEXO ameliorated VSMC senescence by inhibiting mitochondrial fission via regulation of the MST4/ERK/Drp1 signaling pathway. Overexpression of miR-19b-3p in AMEXO improved their beneficial effect on AAA formation. Our study reveals that MSC-exosomal miR-19b-3p exerts protective effects against Ang II-induced AAA and VSMC senescence via regulation of the MST4/ERK/Drp1 pathway. The pathological state of AAA patients alters the miRNA components of AMEXO and impairs their therapeutic benefits.